2012
DOI: 10.1089/end.2011.0619
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Clips Are Safe and a Great Cost-Effective Technique for Arterial and Venous Control in Laparoscopic Nephrectomy: Single-Center Experience with 1834 Laparoscopic Nephrectomies

Abstract: Hem-o-lok and metallic vascular clips applied properly by trained surgeons according to published safety measures provide a safe and considerable cost-saving option for vascular control in laparoscopic nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Equally strong arguments have been published for the use of Hemolok clips. [14,15] Endovascular transfixing stapler devices are not without problems. Chan et al [16] and Deng et al [17] reviewed their own cases and the literature and found two donor deaths as a consequence of stapler failure.…”
Section: Discussionmentioning
confidence: 99%
“…Equally strong arguments have been published for the use of Hemolok clips. [14,15] Endovascular transfixing stapler devices are not without problems. Chan et al [16] and Deng et al [17] reviewed their own cases and the literature and found two donor deaths as a consequence of stapler failure.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques have been used to secure the renal artery and vein during laparoscopic nephrectomy (like Hem-o-lock clips, titanium clips or Vascular Stapler) [14][15][16], but ligation and division of the renal hilum are critical steps during any procedure with any techniques of vascular control for the risks of serious complications [17,18]. EndoGIA staplers are widely used to manage vessels in laparoscopic nephrectomy because of their feasibility and safety and their use has become standard practice [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…staplers) (12). When staplers were compared to Hem-o-lok 1 clips in a center in Iran, the clips cost $20 per donor, while a stapler cost $690 per donor (10). However, from a societal perspective, the laparoscopic procedure is cost-efficient 2 Any kind of re-intervention such as re-stapling, re-clipping, oversew.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that no complication was clearly related to failure of vascular clips. They concluded that clips, when applied by trained surgeons and according to published safety guidelines, provide a safe and cost-saving option for vascular control in LDNs (10). However, the most recent published article in 2009 on FDA reported technical failures of vascular control techniques suggests the opposite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation